Evangelisation or repentance? The re-Christianisation of the Peloponnese in the ninth and tenth centuries - Dunn, Marilyn ca. 20./21. Jh. (Studies in church history, 1977)
Despite its attendant manifestations of renewal, the process of the re-Christianisation of the Peloponnese during the ninth and tenth centuries has not generally been viewed in the context of a renaissance. The remarkable upsurge in church-building in the province from the end of the tenth century onwards, the approximate beginnings of which are marked by the appearance of a large church on the Spartan acropolis, has had its causes ascribed to movements other than the re-vitalisation of religious life in the area. It is true that the great period of church-building in the Peloponnese occurs at a later date than the comparable flourishing in Hellas, where the famous churches of Skripou, of Gregory the Theologian at Thebes, and of John the Baptist in Athens were all built in the ninth century. The late date of this architectural activity has doubtless been one factor which has led some historians to hold an unnecessarily complicated and even untenable view of the impulses which lay behind it.